(untitled) (ACME, 2023)
The examination of a passage from the Diogenes’ Book 3 (Plato’s life 2) – and of parallel places referable to the same tradition – allows us to focus on a crucial mythical motif in the stories about the competition between a human being and a divinity in the gamos with a mortal: the god forbids his mortal antagonist to have sex with the woman who is carrying his divine seed in her womb, until the heroine has completed her pregnancy. The stories of women guilty of double gamos – first with a god and then, shortly after, with a mortal – deal with the harmful consequences of the second contaminating sexual intercourse: one above all is the case of Coronides mother of Asclepius (and perhaps the motif was also associated with other well-known mythical mothers, such as Ariadne, Semele and Alcmena). In these examples, however, the theme of divine prohibition is generally not explicit, as is the case of the bios of Diogenes Laertius. Here Apollo, after conceiving Plato with Perictione, appears to Ariston in order to forbid him any sexual intercourse with the parthenos.